A rare case of Cushing syndrome with virilization - Hossain, Md Solaiman; Jahan, Sharmin; Sultana, Nusrat; Rana, Md Sohel; Debnath, Bidyut Chandra; Hasanat, Muhammad Abul; Fariduddin, Md (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Cortisol, aldosterone, and androgen are synthesized in the adrenal cortex in different enzymatic processes. Adrenocortical carcinoma is usually a co-secreting tumor, whereas adrenal adenoma is rarely co-secreting. A 10-year-old girl presented with progressive hair growth over the face, upper back, lower back, buttocks, upper and lower limbs (arm and thigh) and pubis, significant weight gain, and deepening of voice for 6 months. Clinical examination revealed a puffy and plethoric face, acne, hirsutism and acanthosis nigricans. She was obese and hypertensive. Tanner stage: B1, P4 and Prader stage: I. There was clitoromegaly. Lab study revealed elevated 24-hour urinary free cortisol with low normal ACTH. In addition, there was markedly elevated total testosterone and DHEA-S. CT abdomen showed a large soft tissue mass at the right suprarenal region. She underwent right-sided open adrenalectomy. Histopathology showed benign encapsulated neoplasm with no atypical mitosis, necrosis, vascular invasion, sinusoidal invasion or capsular invasion. Immunohistochemistry revealed Ki67 of about 1% which corresponds with benign adrenal adenoma. Postoperatively she was on a physiological dose of steroid replacement. Clitoromegaly spontaneously regressed after about four months and hirsutism disappeared after about six months. Her biochemical parameters also became normal at 8 months following surgery. J Assoc Clin Endocrinol Diabetol Bangladesh, January 2023; 2 (1): 28-31